The Relationship between Personality Type and Learning Motivation in VIII Semester Student Nursing Program Faculty of Medicine Udayana University. - A. A. Sagung Citra Kumala (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Student learning motivation is a situation from the student themselves that encourages and directing students behavior to the goal they want to be achieved in higher education or college. With a strong learning motivation, the learning process can be run well so that learning achievement could increase. There are many factors that can influence student learning motivation, one of them is personality type. Personality type is an overall pattern of thoughts, feelings, and behaviors that are frequently used in the continuous adaptation of person’s life. This research aims to determine the relationship between personality types with learning motivation in VIII Semester Student Nursing Program Faculty of Medicine Udayana University. This study is a descriptive correlation study using cross-sectional approach. The sampling technique is total sampling with 69 samples of respondents. Data was collected by using a personality questionnaire from Minnesota Multiphasic Personality Inventory (MMPI) with Indonesian language and learning motivation questionnaire that made ??by researchers and have tested by validity and reliability test. The research found that respondents with extroverted personality are 48 people (69.57%) and respondents with introverted personality are 21 people (30.43%). Respondents with high learning motivation are 40 people (58%), moderat learning motivation are 29 people (42%) and no respondents with low learning motivation. Based on a statistical test using the Contingency Coefficient test with ? = 0.05, was found the value of p = 0.000 and r = 0.545, it means the research hypothesis is accepted (p < ?). The conclusion of this research is there are a strong significant relationship between personality type and learning motivation in VIII Semester Student Nursing Program Faculty of Medicine Udayana University.